2009
DOI: 10.1029/2008jd011104
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between diurnal temperature range and surface solar radiation in Europe

Abstract: [1] The surface solar radiation (SSR) is an important factor influencing the local and global energy budget. However, information on the spatial and temporal variation of SSR is limited. A more commonly available measure, which may provide such information, is the diurnal temperature range (DTR). In this study we analyze the relationship between DTR and SSR in Europe between 1970 and 2005 on seasonal and decadal scale. When comparing the mean anomalies time series composed of 31 pairs of sites with long-term S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 52 publications
12
70
0
1
Order By: Relevance
“…After the late 1950s, it began to decrease until the 1980s, and since the 1990s increased. These variations of DTR are consistent with those of observed R s (6,24,30). The better agreement of warm-season variability of DTR with that of R s is consistent with the larger R s during warm seasons.…”
Section: Significancesupporting
confidence: 79%
See 2 more Smart Citations
“…After the late 1950s, it began to decrease until the 1980s, and since the 1990s increased. These variations of DTR are consistent with those of observed R s (6,24,30). The better agreement of warm-season variability of DTR with that of R s is consistent with the larger R s during warm seasons.…”
Section: Significancesupporting
confidence: 79%
“…S3). The agreement between regional DTR and R s over Europe has also been confirmed by both data analysis (10) and model simulation (24). In China, the decrease of R s is in good agreement with the reduction of DTR before 1990 (11).…”
Section: Significancesupporting
confidence: 65%
See 1 more Smart Citation
“…Wild et al (2007) found a strong connection in the observations between changes in DTR and those in surface solar radiation (from dimming to brightening) during the 1980s and with the increasing GHGs. Liu et al (2004) and Makowski et al (2009) reported a similar DSW-DTR connection. Considering the substantial spatiotemporal variability in cloud cover and precipitation, Zhou et al (2008) suggest that enhanced GHGs and aerosols as a steady and global forcing are likely to largely determine the observed long-term DTR trends at large spatial scales.…”
Section: Discussionmentioning
confidence: 65%
“…These include for example their implications for evaporation changes (Wang et al, 2010), for changes in the intensity of the global water cycle (Wild, 2012), for global warming and diurnal temperature range Makowski et al, 2009;Wang and Dickinson, 2013a), for changes in isoprene emissions (Stavrakou et al, 2014), and for glacier melt Huss et al, 2009). Further, GEBA data were used for the assessment of the worldwide variation in diffuse and direct shortwave radiation of relevance for biosphere growth, agricultural production, and tree-ring density (Mercado et al, 2009;Wild et al, 2012;Stine and Huybers, 2014).…”
Section: Implications For Climate Change and Applied Studiesmentioning
confidence: 99%